Joining of plastic by using low power CO2 laser - Mohd Kasmawi, Harun (2012)
Very less work has been done on laser welding of polymer materials. This project related to the optimization of process parameters in laser welding operations. Larger pieces of Polycarbonates were cut into small pieces. The dimension of small pieces is 80 mm × 50 mm × 2 mm were cut from larger pieces. Good surface finish required for laser welding. So the small pieces must not have a gap when it is placed nearly between one another. The small pieces were machined by bend saw machine. Very less burr can also affect the welding output. The small pieces were welded on the welding table. Experimental design using the Taguchi method. Based on the Taguchi method, the number of experiments can be reduced from the total actual experiment. For the analysis, tensile test and microstructural tests were performed on each specimen. This analysis is also based on the Taguchi method calculation. Finally, the optimum parameters for the tensile test and bubble size have been predicted.